SCREENING OF NEROLI OIL ON PARACETAMOL INDUCED HEPATOTOXICITY IN RATS - PATIL, ANNASAHEB; SHIVATHAYA, NEHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to evaluate the hepatoprotective effect of Neroli oil against Paracetamol induced liver injury in Wistar rats. Methods: Changes in the serum biomarker enzymes, namely, alanine transferase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), direct bilirubin, total bilirubin, total cholesterol, and albumin were estimated. Oxidative stress parameter such as MDA, SOD, GSH, and catalase levels was also estimated along with the liver weight and volume. Results: Neroli oil showed significant reduction in all elevated biochemical parameters (namely, ALT, AST, ALP, direct bilirubin, total bilirubin, and total cholesterol), and significant increase in reduced level of albumin. Oil showed significant increase in GSH and catalase level and decreased in LPO level. Histopathological determinations confirmed biochemical findings. Conclusion: Neroli oil showed a significant hepatoprotective effect against Paracetamol induced hepatic damage as depicted by its protective activity on functional, physical, biochemical, antioxidant, and histological changes in liver.